2017
DOI: 10.1093/annweh/wxx067
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study: The UNC Passive Aerosol Sampler in a Working Environment

Abstract: Particle mass concentrations appear to be underestimated by the UNC sampler compared to impactors, more so for PM2.5 than for PM10. CT may be preferred as a collection surface because the blank values were lower and less variable than for PC. Future validations in the working environment should include respirable dust sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…Compared to the deposition model based solely on functions derived from physics, the model with gives more weight to large particles and less to small particles. Based on our and others’ previous observations of low estimates for small particles ( Shirdel et al , 2017 ) and the fact that the wind speed was low in the present environments, an alternative expectation is that the only restriction from the mesh cap is the open area versus the closed area.…”
Section: Methodsmentioning
confidence: 56%
See 1 more Smart Citation
“…Compared to the deposition model based solely on functions derived from physics, the model with gives more weight to large particles and less to small particles. Based on our and others’ previous observations of low estimates for small particles ( Shirdel et al , 2017 ) and the fact that the wind speed was low in the present environments, an alternative expectation is that the only restriction from the mesh cap is the open area versus the closed area.…”
Section: Methodsmentioning
confidence: 56%
“…In a pilot study, the UNC sampler’s performance was compared to impactors in a mine ( Shirdel et al , 2017 ). It showed promising results for particles above 2.5 µm, but indicated large underestimations for PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…The previous two studies [11][12] where the samplers had been grounded, showed homogeneous distributions of particles on all collection surfaces. Static electricity could also be a possible explanation for the higher particle surface loading along the edge observed in this study, which might be due to an imbalance of charges leading the particles to the edge of the sampler where the electric field is strongest.…”
Section: Discussionmentioning
confidence: 83%
“…[5][6][7][8][9][10] There are two previous reports using the UNC sampler in the same working environment as in the present study. [11,12] These studies showed that stationary sampling with the UNC sampler was possible for PM 2.5 , respirable fraction, and PM 10 in the mine, which is an open-pit mine. In Shirdel et al, [12] a new model (area factor) was presented that did not consider the effects from wind because of the windless conditions in the mine.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of passive samplers for the collection of particles is more challenging. When the University of North Carolina passive air sampler was deployed 15 in a working mine, the airborne mass concentrations measured were only 24-35% (PM 2.5 ) and 39-58% (PM 10 ) of those measured at the same time by pumped sampling onto filters.…”
Section: Sampling Techniquesmentioning
confidence: 99%